A lubricating oil high temperature antioxidant and preparation method thereof
By loading and modifying antioxidant molecules with functional auxiliary agents composed of carbon nanotubes and porous ceramic powder in lubricating oil, the problem of difficult synergistic effects of multiple antioxidants in high temperature environments is solved, and lubrication is achieved Excellent stability and antioxidant effect of oil high-temperature antioxidant in high-temperature chain oil.
Patent Information
- Application Number
- CN202410879954.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-02
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-07-02
AI Technical Summary
The combination of multiple antioxidants in existing lubricants is difficult to effectively exert the synergistic effect under high temperature environments, resulting in limited antioxidant performance of high-temperature chain oil.
Using functional auxiliary agent composed of carbon nanotubes and porous ceramic powder, the antioxidant molecules are loaded through its three-dimensional network skeleton structure, and the thermal stability and migration resistance are improved through modification treatment, thereby adjusting in a high-temperature environment. and promote the coordinated cooperation of multiple antioxidants.
It significantly improves the stability and antioxidant effect of lubricating oil high-temperature antioxidants in high-temperature chain oil, extends the service life and improves the normal operation ability of the machinery and equipment.
Smart Images

Figure BDA0004924202480000061 
Figure BDA0004924202480000071 
Figure BDA0004924202480000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lubricating oil antioxidants, and more specifically, to a lubricating oil high-temperature antioxidant and a preparation method thereof. Background Art
[0002] Lubricating oil is a liquid or semi-solid lubricant used in various types of automobiles and mechanical equipment to reduce friction and protect machinery and processed parts. It mainly plays the roles of lubrication, auxiliary cooling, rust prevention, cleaning, sealing and buffering.
[0003] Among them, the high-temperature chain oil in the lubricating oil can protect the lubricating chain at high temperature, reduce the noise when the chain is running, and bring anti-corrosion and anti-rust effects. It is suitable for precision instruments, mechanical parts under high temperature conditions, heavy-duty and high-load equipment, etc. However, the temperature of the high-temperature chain transmission system is maintained at 210-230℃ for a long time, and some are even as high as 250℃, which requires high high-temperature anti-coking performance and evaporation loss performance of the chain oil. Therefore, antioxidants are used in high-temperature chain oil to capture free radicals and prevent the occurrence of free radical reaction chains, thereby protecting the high-temperature chain oil from oxidation, thereby effectively extending the service life of the high-temperature chain oil and maintaining the normal operation of machinery and equipment.
[0004] Currently, the antioxidants commonly used in lubricating oils include phenolic antioxidants, amine antioxidants, sulfide antioxidants and ester antioxidants. In use, multiple types of antioxidants are often used in combination to cope with the complex use environment of high-temperature chain oils.
[0005] Regarding the above-mentioned related technologies, the inventors believe that although the combined use of multiple antioxidants can improve the antioxidant performance to a certain extent, the combination and compatibility between them is poor. Especially in high temperature environments, the synergistic effect between multiple antioxidants is difficult to effectively exert and often fails to achieve expectations. As a result, the effect on high-temperature chain oil after application is also limited.
[0006] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the invention
[0007] In order to enable various combinations of antioxidants to exert excellent synergistic effects under high temperature conditions, the present application provides a lubricating oil high-temperature antioxidant and a preparation method thereof.
[0008] In the first aspect, the present application provides a lubricating oil high temperature antioxidant, which adopts the following technical solution:
[0009] A lubricating oil high-temperature antioxidant is prepared from the following raw materials in parts by weight:
[0010] 5-15 parts of ST-1010 antioxidant;
[0011] L01 antioxidant 15-30 parts;
[0012] L115 antioxidant 25-35 parts;
[0013] 25-35 parts of ST-168 antioxidant;
[0014] 5-8 parts of functional auxiliary agent;
[0015] The functional auxiliary agent consists of carbon nanotubes and porous ceramic powder, and the weight ratio of the carbon nanotubes to the porous ceramic powder is 1:(1.5-2.3).
[0016] By adopting the above technical scheme, the antioxidant system composed of ST-1010 antioxidant, L01 antioxidant, L115 antioxidant and ST-168 antioxidant has good color stability, low evaporation, significantly longer oxidation induction period and better compatibility with high temperature chain oil. In the lubricating oil high temperature antioxidant, carbon nanotubes and porous ceramic powder are used as functional auxiliary agents in the antioxidant system. Carbon nanotubes with multi-layer shell structure and porous ceramic powder with rich pore structure are matched to form a three-dimensional network skeleton structure that is interpenetrating and stacked, forming a good load for antioxidant molecules, and using its own high thermal stability, it can significantly improve the thermal stability and migration resistance of antioxidant molecules, thereby reducing the loss of antioxidants in high temperature environments and significantly improving the duration of antioxidant action. At the same time, the combination of carbon nanotubes and porous ceramic powder has a regulating and promoting effect on the synergistic combination of multiple antioxidants, effectively avoiding the loss of antioxidant efficacy, thereby enabling multiple combinations of antioxidants to exert excellent synergistic effects under high temperature environments. Therefore, the lubricating oil high-temperature antioxidant obtained in this application has excellent and stable application quality in high-temperature chain oils.
[0017] Preferably, the weight ratio of the carbon nanotubes to the porous ceramic powder is 1:2.
[0018] By adopting the above technical scheme, when the carbon nanotubes and porous ceramic powders in the above weight ratio are used in combination, the effect of their mutual cooperation is relatively excellent and stable, and multiple pairs of combinations of antioxidants can also bring better auxiliary effects, thereby enabling the final lubricating oil high-temperature antioxidant to exert better antioxidant effects under high-temperature environments.
[0019] Preferably, the carbon nanotubes are subjected to modification treatment before use, comprising the following steps:
[0020] S1, mixing carbon nanotubes and sulfur powder in a weight ratio of 1:(3.5-4.5), and heating and stirring under nitrogen protection to react to obtain pretreated powder;
[0021] S2. Disperse the pretreated powder in an ethanol solution to obtain a 1.8-2.5 mg / mL pretreated powder dispersion, then add sodium borohydride and polyethyleneimine for ultrasonic dispersion reaction, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1:(2.5-3.5):(15-25), and finally obtain modified carbon nanotubes by centrifugation, washing and drying.
[0022] By adopting the above technical scheme, in the process of modifying carbon nanotubes, sulfur powder is first used for reaction, and a ring-opening reaction is formed on the surface of carbon nanotubes through elemental sulfur, and then sodium borohydride and polyethyleneimine are introduced. On the one hand, sodium borohydride is used for reduction to connect thiol groups to the surface of carbon nanotubes, and on the other hand, polyethyleneimine is used to chemically bond or physically adsorb to the surface of carbon nanotubes, thereby modifying the surface of carbon nanotubes to obtain modified carbon nanotubes. When the modified carbon nanotubes are applied to high-temperature antioxidants for lubricating oils, their carrying capacity for antioxidant molecules at high temperatures when combined with porous ceramic powders is more stable, thereby helping to improve the antioxidant effect of high-temperature antioxidants for lubricating oils in high-temperature chain oils.
[0023] Preferably, in step S2, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1:3:20.
[0024] By adopting the above technical scheme, the raw materials in the above weight ratio can have a better interaction effect during the reaction process, and the modified carbon nanotubes obtained also have a better surface modification effect, and then the corresponding effect exerted in a high temperature environment after application is also relatively excellent, which is conducive to obtaining a high-temperature antioxidant for lubricating oil with better quality.
[0025] Preferably, the porous ceramic powder is modified before use, comprising the following steps:
[0026] The porous ceramic powder is placed in a rare earth mixture with a concentration of 0.4-0.6 mol / L, the material-liquid ratio of the porous ceramic powder to the rare earth mixture is 1 g:(10-15) ml, after shaking reaction, filtering and drying, and sintering at 500-600°C for 1.5-2.5 hours to obtain the modified porous ceramic powder.
[0027] By adopting the above technical scheme, in the process of modifying the porous ceramic powder, a rare earth mixed liquid is used, and the number of active groups on the surface and inside of the porous ceramic powder is increased through the rare earth elements, and the surface is greatly improved, so that after the modified porous ceramic powder is used, it is not only easier to cooperate with carbon nanotubes to play an excellent role, but also can cooperate with antioxidant molecules to show better compatibility with high-temperature chain oil, thereby significantly improving the overall antioxidant effect brought about by the application of high-temperature antioxidants in lubricating oils.
[0028] Preferably, the rare earth mixed solution is a lanthanum-cerium mixed solution, and the molar ratio of lanthanum to cerium is 1:1.
[0029] By adopting the above technical scheme, the rare earth mixed liquid composed of lanthanum and cerium in the above molar ratio has a better surface modification effect on the porous ceramic powder during the modification process of the porous ceramic powder. The obtained modified porous ceramic powder has strong resistance to migration and controllability of antioxidant molecules in high temperature environment, thereby enabling various combinations of antioxidants to exert excellent synergistic effects in high temperature environment, and finally obtaining a high-temperature antioxidant for lubricating oil with better quality.
[0030] Preferably, the carbon nanotubes have a diameter of 60-100 nm and a length of 1-2 μm; the porous ceramic powder has a particle size of 30-50 nm and a pore size of 5-15 nm.
[0031] By adopting the above technical scheme, when the carbon nanotubes and porous ceramic powders of the above specifications are combined, part of the porous ceramic powder will enter the carbon nanotubes, and form a relatively rich three-dimensional network skeleton structure with the porous ceramic powder adhered to the surface of the carbon nanotubes, which can form a multi-level load for the antioxidant molecules, and then can play an excellent auxiliary role in the synergistic combination of multiple antioxidants, so that the high-temperature antioxidant of the lubricating oil can play a better antioxidant effect in the high-temperature chain oil.
[0032] Preferably, the carbon nanotubes have a diameter of 80 nm and a length of 1.5 μm; the porous ceramic powder has a particle size of 35 nm and a pore size of 10 nm.
[0033] By adopting the above technical solution, the carbon nanotubes and porous ceramic powders of the above specifications are more completely matched with each other, and the corresponding effects brought about are also more excellent, so that a high-temperature antioxidant for lubricating oil with better quality for use in high-temperature environments can be obtained.
[0034] In a second aspect, the present application provides a method for preparing a high-temperature antioxidant for lubricating oil, using the following technical solution: A method for preparing a high-temperature antioxidant for lubricating oil, comprising the following steps:
[0035] (1) preparing raw materials including ST-1010 antioxidant, L01 antioxidant, L115 antioxidant, ST-168 antioxidant and functional auxiliary agent according to the proportion;
[0036] (2) The ST-1010 antioxidant, L01 antioxidant, L115 antioxidant, ST-168 antioxidant and functional auxiliary agent in step (1) are stirred and mixed to obtain a lubricating oil high temperature antioxidant.
[0037] By adopting the above technical scheme, the above preparation method is simple to operate, and the functional auxiliary agent can complete the loading of the antioxidant molecules only through simple mixing, and can exert excellent effects after application. It is not only suitable for large-scale industrial production, but also the overall quality of the obtained lubricating oil high-temperature antioxidant is relatively excellent and stable.
[0038] In summary, this application has the following beneficial effects:
[0039] 1. The functional auxiliary agent composed of carbon nanotubes and porous ceramic powder is used in the present application. Through the coordination between the nanotubes and the porous ceramic powder, the coordination between various antioxidants is regulated and promoted, effectively avoiding the loss of antioxidant efficacy, thereby enabling various combinations of antioxidants to exert excellent synergistic effects under high temperature environments, and the obtained lubricating oil high-temperature antioxidant can also exert excellent and stable antioxidant effects in high-temperature chain oils;
[0040] 2. The present application modifies carbon nanotubes and porous ceramic powders so that after application, the modified porous ceramic powders and modified carbon nanotubes can not only cooperate with antioxidant molecules to show better compatibility with high-temperature chain oils, but also can make the carrying capacity of antioxidant molecules more stable at high temperatures, thereby significantly improving the antioxidant effect of the high-temperature antioxidants in lubricating oils used in high-temperature chain oils. DETAILED DESCRIPTION
[0041] The present application is further described in detail below in conjunction with preparation examples and embodiments.
[0042] Unless otherwise specified, the raw materials used in the preparation examples and embodiments of the present application are commercially available:
[0043] Multi-walled carbon nanotubes were purchased from Zhongke Leiming, CAS No. 308068-56-6.
[0044] Preparation examples of raw materials and / or intermediates
[0045] Preparation Example 1
[0046] A modified carbon nanotube is prepared by the following steps:
[0047] S1, mixing carbon nanotubes and sulfur powder in a weight ratio of 1:4, and heating and stirring under nitrogen protection for reaction, stirring at 400 r / min, and reacting at 180° C. for 10 h to obtain pretreated powder;
[0048] S2. Disperse the pretreated powder in an ethanol solution to obtain a 2.1 mg / mL pretreated powder dispersion, then add sodium borohydride and polyethyleneimine for ultrasonic dispersion reaction for 12 hours, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1:3:20, and finally obtain modified carbon nanotubes by centrifugation, washing and drying.
[0049] Note: The carbon nanotubes used are multi-walled carbon nanotubes with a diameter of 80 nm and a length of 1.5 μm.
[0050] Preparation Example 2
[0051] A modified carbon nanotube, which is different from Preparation Example 1 in that, in step S2, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1:2.5:15.
[0052] Preparation Example 3
[0053] A modified carbon nanotube, which is different from Preparation Example 1 in that, in step S2, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1:3.5:25.
[0054] Preparation Example 4
[0055] A modified carbon nanotube, which is different from Preparation Example 1 in that it is prepared by the following steps:
[0056] S1, mixing carbon nanotubes and sulfur powder in a weight ratio of 1:3.5, and heating and stirring under nitrogen protection for reaction, stirring at 400 r / min, and reacting at 180° C. for 10 h to obtain pretreated powder;
[0057] S2. Disperse the pretreated powder in an ethanol solution to obtain a 2.5 mg / mL pretreated powder dispersion, then add sodium borohydride and polyethyleneimine for ultrasonic dispersion reaction for 12 hours, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1:3:20, and finally obtain modified carbon nanotubes by centrifugation, washing and drying.
[0058] Preparation Example 5
[0059] A modified carbon nanotube, which is different from Preparation Example 1 in that it is prepared by the following steps:
[0060] S1, mixing carbon nanotubes and sulfur powder in a weight ratio of 1:4.5, and heating and stirring under nitrogen protection for reaction, stirring at 400 r / min, and reacting at 180° C. for 10 h to obtain pretreated powder;
[0061] S2. Disperse the pretreated powder in an ethanol solution to obtain a 1.8 mg / mL pretreated powder dispersion, then add sodium borohydride and polyethyleneimine for ultrasonic dispersion reaction for 12 hours, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1:3:20, and finally obtain modified carbon nanotubes by centrifugation, washing and drying.
[0062] Preparation Example 6
[0063] A modified porous ceramic powder is prepared by the following steps:
[0064] The porous ceramic powder was placed in a rare earth mixture with a concentration of 0.5 mol / L. The material-liquid ratio of the porous ceramic powder to the rare earth mixture was 1 g:12.5 ml. After shaking reaction for 24 hours, the powder was filtered and dried, and then sintered at 550°C for 2 hours to obtain the modified porous ceramic powder.
[0065] Note: The porous ceramic powder used is silicon nitride ceramic powder, with a particle size of 35 nm and a pore size of 10 nm; the rare earth mixed solution is a lanthanum-cerium mixed solution, and the molar ratio of lanthanum to cerium is 1:1.
[0066] Preparation Example 7
[0067] A modified porous ceramic powder, which is different from Preparation Example 6 in that it is prepared by the following steps:
[0068] The porous ceramic powder was placed in a rare earth mixture with a concentration of 0.4 mol / L, the material-liquid ratio of the porous ceramic powder to the rare earth mixture was 1 g:10 ml, and after shaking reaction for 24 hours, it was filtered and dried, and sintered at 500°C for 2.5 hours to obtain the modified porous ceramic powder.
[0069] Preparation Example 8
[0070] A modified porous ceramic powder, which is different from Preparation Example 6 in that it is prepared by the following steps:
[0071] The porous ceramic powder was placed in a rare earth mixture with a concentration of 0.6 mol / L. The material-liquid ratio of the porous ceramic powder to the rare earth mixture was 1 g:15 ml. After shaking reaction for 24 hours, the mixture was filtered and dried, and sintered at 600°C for 1.5 hours to obtain the modified porous ceramic powder.
[0072] Preparation Example 9
[0073] A modified porous ceramic powder, which is different from Preparation Example 6 in that the rare earth mixed solution does not contain lanthanum.
[0074] Preparation Example 10
[0075] A modified porous ceramic powder, which is different from Preparation Example 6 in that the rare earth mixed solution does not contain cerium.
[0076] Example
[0077] Example 1
[0078] A lubricating oil high temperature antioxidant, the raw materials used for preparation and their corresponding weights are shown in Table 1, and the preparation is obtained by the following steps:
[0079] (1) preparing raw materials including ST-1010 antioxidant, L01 antioxidant, L115 antioxidant, ST-168 antioxidant and functional auxiliary agent according to the proportion;
[0080] (2) The ST-1010 antioxidant, L01 antioxidant, L115 antioxidant, ST-168 antioxidant and functional auxiliary agent in step (1) are stirred and mixed in a mixer at 300 r / min for 35 min to obtain a lubricating oil high-temperature antioxidant.
[0081] Note: The functional auxiliary agent is composed of carbon nanotubes and porous ceramic powder, and the weight ratio of carbon nanotubes to porous ceramic powder is 2; the carbon nanotubes are multi-walled carbon nanotubes with a tube diameter of 80nm and a length of 1.5μm; the porous ceramic powder is silicon nitride ceramic powder with a particle size of 35nm and a pore size of 10nm.
[0082] Example 2-3
[0083] A lubricating oil high temperature antioxidant, which is different from Example 1 in that the raw materials used in the preparation and their corresponding weights are shown in Table 1.
[0084] Table 1 Raw materials used in the preparation of Examples 1-3 and their weight portions (kg / portion)
[0085]
[0086]
[0087] Example 4
[0088] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the weight ratio of carbon nanotubes to porous ceramic powder is 1:1.5.
[0089] Example 5
[0090] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the weight ratio of carbon nanotubes to porous ceramic powder is 1:2.3.
[0091] Example 6
[0092] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the weight ratio of carbon nanotubes to porous ceramic powder is 1:1.9.
[0093] Example 7
[0094] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the carbon nanotubes are replaced by modified carbon nanotubes, and the modified carbon nanotubes are obtained from Preparation Example 1.
[0095] Example 8
[0096] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the carbon nanotubes are replaced by modified carbon nanotubes, and the modified carbon nanotubes are obtained from Preparation Example 2.
[0097] Example 9
[0098] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the carbon nanotubes are replaced by modified carbon nanotubes, and the modified carbon nanotubes are obtained from Preparation Example 3.
[0099] Example 10
[0100] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the carbon nanotubes are replaced by modified carbon nanotubes, and the modified carbon nanotubes are obtained from Preparation Example 4.
[0101] Embodiment 11
[0102] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the carbon nanotubes are replaced by modified carbon nanotubes, and the modified carbon nanotubes are obtained from Preparation Example 5.
[0103] Example 12
[0104] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the porous ceramic powder is replaced by modified porous ceramic powder in mass, and the modified porous ceramic powder is obtained from Preparation Example 6.
[0105] Embodiment 13
[0106] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the porous ceramic powder is replaced by modified porous ceramic powder in mass, and the modified porous ceramic powder is obtained from Preparation Example 7.
[0107] Embodiment 14
[0108] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the porous ceramic powder is replaced by modified porous ceramic powder in mass, and the modified porous ceramic powder is obtained from Preparation Example 8.
[0109] Embodiment 15
[0110] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the porous ceramic powder is replaced by modified porous ceramic powder, and the modified porous ceramic powder is obtained from Preparation Example 9.
[0111] Example 16
[0112] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the porous ceramic powder is replaced by modified porous ceramic powder in mass, and the modified porous ceramic powder is obtained from Preparation Example 10.
[0113] Embodiment 17
[0114] A high-temperature antioxidant for lubricating oil, which differs from Example 1 in that an equal amount of carbon nanotubes is replaced by modified carbon nanotubes, and the modified carbon nanotubes are obtained from Preparation Example 1; an equal amount of porous ceramic powder is replaced by modified porous ceramic powder, and the modified porous ceramic powder is obtained from Preparation Example 6.
[0115] Embodiment 18
[0116] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the diameter of the carbon nanotube is 60nm and the length is 1μm; the particle size of the porous ceramic powder is 30nm and the pore size is 5nm.
[0117] Embodiment 19
[0118] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the diameter of the carbon nanotube is 100 nm and the length is 2 μm; the particle size of the porous ceramic powder is 50 nm and the pore size is 15 nm.
[0119] Comparative Example
[0120] Comparative Example 1
[0121] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the functional auxiliary agent does not contain carbon nanotubes.
[0122] Comparative Example 2
[0123] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the functional auxiliary agent does not contain porous ceramic powder.
[0124] Comparative Example 3
[0125] A lubricating oil high-temperature antioxidant, which is different from Example 1 in that the raw materials do not contain functional auxiliary agents.
[0126] Performance test samples: The lubricating oil high temperature antioxidant obtained in Example 1-19 was used as test sample 1-19, and the lubricating oil high temperature antioxidant obtained in Comparative Example 1-3 was used as control sample 1-3.
[0127] Test method: 250SN base oil was used as the test oil, 1.2% of test samples 1-19 and control samples 1-3 were added respectively, and then 30 test samples were obtained.
[0128] (1) For 22 test samples, an oxidation induction period test was conducted at a high temperature of 240°C. Each test sample was measured 3 times, and the average value corresponding to test samples 1-19 and control samples 1-3 was recorded in Table 2;
[0129] (2) The evaporation capacity of 22 test samples was tested at a high temperature of 250°C. The evaporation capacity after 9 hours and 18 hours was tested. The corresponding test samples 1-19 and control samples 1-3 are recorded in Table 2;
[0130] (3) For the 22 test samples, the color difference values before and after being placed at a high temperature of 250°C for 12 hours were tested using a DS-200 precision colorimeter. The corresponding results were recorded in Table 2 for test samples 1-19 and control samples 1-3.
[0131] Table 2 Test results of test samples 1-19 and control samples 1-3
[0132]
[0133]
[0134] Combining Examples 1-6 and Comparative Examples 1-3 and Table 2, it can be seen that the use of the functional adjuvant composed of carbon nanotubes and porous ceramic powder makes the lubricating oil high temperature antioxidant used in the base oil have a longer 240°C oxidation induction period, and the 9h evaporation amount (%), 18h evaporation amount (%) and color difference value (ΔE) are all close. It can be seen that the various antioxidant molecules in the lubricating oil high temperature antioxidant can exert excellent synergistic effects under high temperature environment, and the antioxidant effect is outstanding; at the same time, if any one of the carbon nanotubes and porous ceramic powder is used alone as a functional adjuvant, it is found that the corresponding improvement effect is limited, and is far less than the excellent effect brought by the combination of the two; among them, when the weight ratio of carbon nanotubes to porous ceramic powder is 1:2, the lubricating oil high temperature antioxidant obtained by the application of the functional adjuvant has better quality.
[0135] Combining Example 1 and Example 7-11 with Table 2, it can be seen that the use of modified carbon nanotubes can be combined with porous ceramic powder to stabilize the carrying capacity of antioxidant molecules at high temperature, thereby making the lubricating oil high-temperature antioxidant show a more excellent antioxidant effect after application. The 240°C oxidation induction period value obtained by testing becomes longer, and the 9h evaporation amount (%), 18h evaporation amount (%) and color difference value (ΔE) are significantly reduced. Among them, in the modification process of carbon nanotubes, when the weight ratio of pretreated powder, sodium borohydride and polyethyleneimine is 1:3:20, the improvement effect of the modified carbon nanotube application is relatively excellent.
[0136] Combining Example 1 and Example 12-16 and Table 2, it can be seen that the use of modified porous ceramic powder can be more easily matched with carbon nanotubes, and the antioxidant molecules show better compatibility with high-temperature chain oil, thereby making the lubricating oil high-temperature antioxidant show a more excellent antioxidant effect after application. The 240°C oxidation induction period value obtained by testing becomes longer, and the 9h evaporation amount (%), 18h evaporation amount (%) and color difference value (ΔE) are significantly reduced. Among them, in the process of modifying the porous ceramic powder, the rare earth mixed liquid is selected as a lanthanum-cerium mixed liquid, and the molar ratio of lanthanum and cerium is 1:1, which can make the application of the modified porous ceramic powder have a more excellent lifting effect.
[0137] From Example 1, Example 7, Example 12 and Example 17 and Table 2, it can be seen that when the modified carbon nanotubes and the modified porous ceramic powder are used together, they can exert an excellent compound synergistic effect on each other, bringing a technical effect of 1+1>2, so that the antioxidant effect of the application of high-temperature antioxidants in lubricating oils is significantly improved.
[0138] It can be seen from Example 1 and Examples 18-19 and Table 2 that the diameter of the carbon nanotubes is 60-100nm and the length is 1-2μm; the particle size of the porous ceramic powder is 30-50nm and the pore size is 5-15nm; both can ensure that the two can exert an excellent coordination effect, and then can play an excellent auxiliary role in the synergistic coordination between multiple antioxidants, so that the lubricating oil high temperature antioxidant can exert a better antioxidant effect in the high temperature chain oil.
[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A lubricating oil high temperature antioxidant, characterized in that: Made from the following raw materials in parts by weight: 5-15 parts of ST-1010 antioxidant; L01 antioxidant 15-30 parts; L115 antioxidant 25-35 parts; 25-35 parts of ST-168 antioxidant; 5-8 parts of functional auxiliary agent; The functional auxiliary agent is composed of carbon nanotubes and porous ceramic powder, and the weight ratio of the carbon nanotubes to the porous ceramic powder is 1:(1.5-2.3); The carbon nanotubes are modified before use, comprising the following steps: S1, mixing carbon nanotubes and sulfur powder in a weight ratio of 1:(3.5-4.5), and heating and stirring under nitrogen protection to react to obtain pretreated powder; S2, dispersing the pretreated powder in an ethanol solution to obtain a 1.8-2.5 mg / mL pretreated powder dispersion, then adding sodium borohydride and polyethyleneimine for ultrasonic dispersion reaction, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1: (2.5-3.5): (15-25), and finally centrifuging, washing and drying to obtain modified carbon nanotubes; The porous ceramic powder is modified before use, comprising the following steps: The porous ceramic powder is placed in a rare earth mixed solution with a concentration of 0.4-0.6 mol / L, and the material-liquid ratio of the porous ceramic powder to the rare earth mixed solution is 1 g: (10-15) ml. After shaking reaction, the mixture is filtered and dried, and then sintered at 500-600° C. for 1.5-2.5 hours to obtain a modified porous ceramic powder. The rare earth mixed solution is a lanthanum-cerium mixed solution, and the molar ratio of lanthanum to cerium is 1:
1.
2. The lubricating oil high temperature antioxidant according to claim 1, characterized in that: The weight ratio of the carbon nanotubes to the porous ceramic powder is 1:
2.
3. The lubricating oil high temperature antioxidant according to claim 1, characterized in that: In step S2, the weight ratio of the pretreated powder, sodium borohydride and polyethyleneimine is 1:3:
20.
4. The lubricating oil high temperature antioxidant according to claim 1, characterized in that: The diameter of the carbon nanotube is 60-100nm and the length is 1-2μm; the particle size of the porous ceramic powder is 30-50nm and the pore size is 5-15nm.
5. The lubricating oil high temperature antioxidant according to claim 4, characterized in that: The diameter of the carbon nanotube is 80nm and the length is 1.5μm; the particle size of the porous ceramic powder is 35nm and the pore size is 10nm.
6. The method for preparing the lubricating oil high temperature antioxidant according to claim 1, characterized in that: The following steps are involved: (1) Prepare raw materials including ST-1010 antioxidant, L01 antioxidant, L115 antioxidant, ST-168 antioxidant and functional auxiliary agent according to the proportion; (2) The ST-1010 antioxidant, L01 antioxidant, L115 antioxidant, ST-168 antioxidant and functional auxiliary agent in step (1) are stirred and mixed to obtain a lubricating oil high temperature antioxidant.
Citation Information
Patent Citations
Lubricating oil high-temperature antioxidant, lubricating oil and preparation method of lubricating oil
CN116083139A
Composite lubricating grease and preparation method thereof
CN117660078A